Youth in agriculture: A PhotoVoice perspective to envision their engagement in agricultural practices - Shijagurumayum, Meghajit; Hakhu, Arunima; Gupta, Shweta; Singh, Sonali; Malaiappan, Sudharsan; Kumar, Gopal; Rietveld, Anne; Borah, Gulshan; Sikka, Alok (2024)
This report examines youth engagement in agriculture, focusing on agroecology in Mandla district, Madhya Pradesh. Despite agriculture's critical role in livelihoods, rural youth show declining interest due to perceptions of low profitability, high risks, and systemic barriers like limited land ownership and inadequate institutional support. Using the PhotoVoice methodology, the study captures youth aspirations, challenges, and perceptions of sustainable farming practices. Findings indicate that while young women and men value agroecology's benefits—improved soil health, sustainability, and income—they face significant hurdles, including resource scarcity, water shortages, and financial constraints. Many envision "dream farms" with modern equipment and sustainable practices but lack the infrastructure and support to realize these goals. Youth also report limited agency in decision-making and minimal participation in collectives, further alienating them from the sector. To address these challenges, the report calls for creating collectives for young women and men for collaboration, enhancing capacity-building programs, and integrating agroecology into education and policy frameworks. Strengthening institutional support, providing financial and technical assistance, and leveraging NGO partnerships are recommended to bridge gaps and empower youth as leaders in agroecological transitions. These actions are essential for fostering a resilient and sustainable agricultural future driven by young farmers.